2010
DOI: 10.1016/j.neulet.2010.08.080
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine selectively increases proliferation in the adult murine hippocampus

Abstract: Cocaine abuse continues to be a significant problem in the USA and elsewhere. Cocaine is an indirect agonist for dopamine, norepinephrine and serotonin with numerous potential downstream effects, including processes and signals associated with adult neurogenesis. Since drug addiction is associated with brain plasticity, we hypothesized that cocaine exposure would alter cellular proliferation in two adult neurogenic regions (the subventricular and subgranular zones). We used bromodeoxyuridine (BrdU) to track ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…On the other hand, some authors have found no effect (Mustroph et al, 2011) or increased neurogenesis from repeated cocaine treatment (Lloyd et al, 2010). Moreover, self-administration of methamphetamine for one hour, twice weekly for approximately 50 days increased numbers of immature neurons as indicated by DCX in rats (Mandyam et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some authors have found no effect (Mustroph et al, 2011) or increased neurogenesis from repeated cocaine treatment (Lloyd et al, 2010). Moreover, self-administration of methamphetamine for one hour, twice weekly for approximately 50 days increased numbers of immature neurons as indicated by DCX in rats (Mandyam et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Among these are neuropeptides, such as endogenous opioids and oxytocin and the neuromodulator dopamine. Some evidence suggests that each of these factors is capable of stimulating the production of new neurons in the hippocampus (Morton et al, 2009; Höglinger et al, 2004; Winner et al, 2009; Lloyd et al, 2010; Koehl et al, 2008; Persson et al, 2003). It is also possible that neurotrophic factors play a role in buffering the brain from the suppressive actions of elevated glucocorticoids.…”
Section: Paradoxical Effects Of Rewarding Experience On Adult Neurogementioning
confidence: 99%
“…In rodent models used to study addiction, repeated exposure to psychostimulants results in behavioral sensitization and accompanying neurobiological changes throughout the brain. Specifically, repeated cocaine exposure produces persistent changes in neuroplasticity, including dendritic remodeling (Robinson and Kolb, 1999, Robinson et al, 2001, Kolb et al, 2003, Li et al, 2004, Robinson and Kolb, 2004, Ferrario et al, 2005) and neurogenesis (Yamaguchi et al, 2004, Dominguez-Escriba et al, 2006, Garcia-Fuster et al, 2010, Lloyd et al, 2010, Noonan et al, 2010), that extend well beyond the period of active drug administration.…”
Section: Introductionmentioning
confidence: 99%